Satisfaction Level from Digital Learning Implementation Using E-Learning Management System (LMS) UP45 at University of Proklamasi 45 - Agung Prayogo; Selvy Dwi Hartiyani; Erlinawaty Hartiyani; Puti Adam Dewi (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
Learning process in campus has undergone several fundamental changes since the COVID-19 pandemic. The face-to-face lectures cannot be fully implemented due to the increasing number of COVID-19 cases. The education sector continues to make some improvisation in learning methods. This study aims to measure the level of operational feasibility of a Moodle-based Learning Management System at University of Proklamasi 45 Yogyakarta. This study used Taro Yamane Formula as the sampling method. There are 1517 total students in the population with a minimum sample of 94 (error margin of 10%) requirement (actual sample = 120). The data were obtained from the dissemination of questionnaires, using linked scales processed using SPSS software. The respondents are the students, lecturers and academic staffs as the person in charge of the e-learning platform UP45. This method resulted in a decision on the use of e-learning along with the operational feasibility of the online learning system implemented at University of Proklamasi 45 Yogyakarta. The general conclusion of this study is that the operational feasibility of E-Learning UP45 Yogyakarta, can be used as a digital learning solution during the Covid-19 pandemic. The valid percentage that supports the implementation and maintenance of an online learning LMS-based is 72.5%.